Risk factors for a differentiation syndrome in patients with acute promyelocytic leukemia - A. A. Semenova; V. V. Troitskaya; I. V. Galtseva; E. N. Parovichnikova (Онкогематология, 2023)
Differentiation syndrome (DS) is a severe complication of acute promyelocytic leukemia and its treatment, which is one of the causes of high early mortality. the similarity of clinical manifestations of DS and other complications that may develop during acute promyelocytic leukemia therapy makes it difficult to diagnose ds. at the same time, untimely initiation of DS therapy with glucocorticosteroids can lead to the patient’s death. The only generally accepted risk factor for ds is initial leukocytosis. Specific markers confirming ds have not yet been found. A number of studies show that in patients with diagnosed DS, the expression of CD56, CD54, CD2, CD15, CD13, markers of immature granulocytes, β2-integrins was more often found on blast cells. exposure to tretinoin increased the expression of chemokine receptors, chemokines, and cytokines by blast cells and vascular endothelium. The influence exerted by atypical promyelocytes, due to their biological characteristics, on the coagulation system suggests an association between hemostasis state and ds development. However, the value of the above markers as predictors or signs of DS still needs to be tested, especially when it comes to non-chemotherapeutic treatment of acute promyelocytic leukemia with arsenic trioxide.